Implementation of Digital Technology to Improve Balance at Elderly Posyandu - Nazhira, Fidyatul; Anggraeni, Risa Kusuma; Faradillah, Kiki Rezki; Rabia, Rabia; Ghani, Gibran; Puspadini, Dinda; Nainggolan, Marcel Geordan; Rifanty, Ananda Putri; Wibisono, Heri (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT This community service initiative was designed to enhance balance among the elderly by leveraging digital technology at Posyandu Lansia RW 06, Rangkapan Jaya Baru, Depok City. The underlying issue was that Indonesia's increasing life expectancy was not accompanied by healthier lifestyle habits, leading to a higher risk of falls. Poor balance among the elderly elevated the likelihood of falls, which could adversely affect their independence and quality of life. The research methodology involved conducting Focus Group Discussions (FGDs) to identify primary concerns, educating participants on the importance of balance, and providing balance exercise training through digital instructional videos. Evaluations were performed using pre-test and post-test assessments. The results indicated a significant improvement in the participants' knowledge. In conclusion, despite challenges like limited access to technology, the program successfully achieved its objectives and showed potential for further development and implementation in other locations. This initiative provided tangible benefits to the elderly, boosting their confidence in daily activities, reducing the risk of falls, and thereby enhancing their overall quality of life. Keywords: Elderly, Balance, Exercise, Technology